PENGEMBANGAN MEDIA PEMBELAJARAN ISPRING SUITE SEBAGAI SUMBER BELAJAR INTERAKTIF PADA MATERI REDOKS - Romadhoni, Siti Dzakiya; Halimah, Nur; Jannah, Raudatul; Mardhiya, Julia (Universitas Tanjungpura, 2024)
The 21st century is characterized by the use of technology, information and communication in various fields of life, one of which is education which is applied in the learning process. Based on observations at MA NU Miftahul Ulum Margasari, it is known that the available and frequently used learning media are in the form of textbooks, worksheets, videos, powerpoints, and audio. This causes the ongoing learning process to appear less attractive to students, thus making students feel bored and have less interest in learning chemistry which has an impact on a passive classroom atmosphere. The purpose of this research is to develop iSpring suite 9 interactive learning media based on android on redox material. The type of research used is development (Development Research) with the Plomp development model. The results showed that the percentage of eligibility based on 4 validators obtained an average value of 81.075% from the appearance aspect, 85% from the feasibility aspect, and 82.475% from the programming aspect. Based on the percentage obtained, it proves that the android-based iSpring Suite 9 learning media is very feasible to try out on students.